2021
DOI: 10.3389/fmicb.2021.680420
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Source Dependent Interplay of Copper and Manganese Ions Modulates the Morphology and Itaconic Acid Production in Aspergillus terreus

Abstract: The effects of the interplay of copper(II) and manganese(II) ions on growth, morphology and itaconic acid formation was investigated in a high-producing strain of Aspergillus terreus (NRRL1960), using carbon sources metabolized either mainly via glycolysis (D-glucose, D-fructose) or primarily via the pentose phosphate shunt (D-xylose, L-arabinose). Limiting Mn2+ concentration in the culture broth is indispensable to obtain high itaconic acid yields, while in the presence of higher Mn2+ concentrations yield dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…We thus consider it possible that-besides inhibiting manganese transport-Cu 2+ can induce the same symptoms of oxidative stress in the presence of manganese that manganese deficiency would cause. In line with this, it was recently described that the ratio of Cu 2+ to Mn 2+ -rather than their respective absolute concentration-determines micro-and macro-morphology of the A. terreus biomass and modulates itaconic acid production yield [32] on the glycolytic carbon sources D-glucose and D-fructose. Inclusion of the Cu 2+ ion concentration amongst the process variables even led to the formulation of growth media for the production of itaconic acid without the need to remove surplus Mn 2+ in advance [58].…”
Section: Metal Ions-related Aspects Of Submerged Organic Acid Fermentationsmentioning
confidence: 69%
See 1 more Smart Citation
“…We thus consider it possible that-besides inhibiting manganese transport-Cu 2+ can induce the same symptoms of oxidative stress in the presence of manganese that manganese deficiency would cause. In line with this, it was recently described that the ratio of Cu 2+ to Mn 2+ -rather than their respective absolute concentration-determines micro-and macro-morphology of the A. terreus biomass and modulates itaconic acid production yield [32] on the glycolytic carbon sources D-glucose and D-fructose. Inclusion of the Cu 2+ ion concentration amongst the process variables even led to the formulation of growth media for the production of itaconic acid without the need to remove surplus Mn 2+ in advance [58].…”
Section: Metal Ions-related Aspects Of Submerged Organic Acid Fermentationsmentioning
confidence: 69%
“…Although it is-as with iron and zinc-required as an essential trace element in many biochemical reactions, it rapidly becomes toxic at concentrations where Fe, Zn and Mn do not, since it inactivates other metalloenzymes by metal displacement, and generates reactive oxygen species by the Fenton reaction [27][28][29] This toxicity of copper is also a means for the competition between organisms, e.g., the innate phagocyte utilizes copper for defence against microbes [30,31]. Sándor et al [32] have recently shown that copper toxicity in A. terreus is dependent on the carbon source and the concentration of Mn.…”
Section: Biology Of First-row Transition Metal Ions In Fungimentioning
confidence: 99%
“…A high-yield citric acid fermentation (shake-flask or bioreactor alike) was defined as a culture reaching a Y p/s of >0.8 (Karaffa et al, 2021). Three aspects of mycelial morphology were monitored by microscopy: 1) swollen, yeast-like hyphae; 2) filamentous hyphae; and 3) pellet-like mycelial clumps (aggregates) (Bartoshevich et al, 1990;Paul and Thomasn, 1998;Sándor et al, 2021). To improve image contrast, lactophenol cotton blue (Fluka Chemie, Buch, Switzerland) at a final concentration of 10% (v/v) was added to the samples.…”
Section: Methodsmentioning
confidence: 99%
“…Several strains are much more efficient in producing AI after a genetic modification. Therefore, these strains, even if they are not originally IA producers, with the introduction of the relevant gene expressions can produce a high IA quantity from various substrates, not just from glucose but also from acetate, lignin, cellobiose, xylose, glycerol (biodiesel waste), and several other substrates [ 41 , 91 ].…”
Section: Itaconic Acid (Ia) Synthesismentioning
confidence: 99%
“…This unsaturated organic acid is an advantageous platform chemical suitable for monomer or during monomer synthesis [ 39 , 40 ]. Important chemical properties can be indexed to the methylene groups’ conjugated double bonds that enable polymerization through condensation and esterification with distinct co-monomers by the carboxylic groups [ 41 , 42 ]. Owing to its multifaceted utilization ( Figure 1 ), these are enclosed in the leading 12 building block chemicals acquired from renewable biomass, agriculture-based wastes, food by-products, municipal solid wastes, or industrial by-products (i.e., glycerol) according to the US Department of Energy [ 39 ].…”
Section: Introductionmentioning
confidence: 99%